Effect of oxalic acid and sodium hydroxide on the desulfurization of coal using UV–H2O2 oxidation system. (2nd January 2022) - Yue, Jinsong; Li, Mei; Ding, Ning; Cheng, Sidan; Gao, Caiyun
Abstract : To research the efficient and economical desulfurization of Lingshi high sulfur coal (LS), the influence of acid and alkaline additives on an ultraviolet (UV) light oxidation desulfurization system was assessed. Sodium hydroxide (NaOH) and oxalic acid (OA) were selected as the alkaline and acid additives, respectively, to investigate whether acid and alkaline additives could promote oxidative desulfurization in the UV–H2 O2 system. The coal samples were investigated via scanning electron microscopy (SEM), Brannuer–Emmett–Teller analysis (BET), contact angle analysis (CA), Fourier transform infrared spectroscopy (FTIR), X-ray diffractometry (XRD), and X-ray photoelectron spectroscopy (XPS). In addition, the desulfurization mechanism, including sulfur removal, sulfur conversion, and change of coal surface morphology on the reaction, was investigated. The results demonstrated that the surface morphology and the pore structure in coal improved; the wettability and oxygen-containing functional groups increased after the action of NaOH and OA, which indicated that the oxidation was enhanced during the reaction. This study proved that strong oxidation promoted the efficient removal of sulfur from coal samples, where NaOH reacted strongly with pyrite, and OA influenced the removal of organic sulfur, which played a directional desulfurization effect. GRAPHICAL ABSTRACT: UF0001